2022
DOI: 10.1038/s43705-022-00180-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the uncharacterised diversity of amphibian and reptile viruses

Abstract: Amphibians and non-avian reptiles represent a significant proportion of terrestrial vertebrates, however knowledge of their viruses is not proportional to their abundance. Many amphibians and reptiles have strict habitual environments and localised populations and are vulnerable to viral outbreaks and potential elimination as a result. We sought to identify viruses that were hidden in amphibian and reptile metatranscriptomic data by screening 235 RNA-sequencing datasets from a 122 species covering 25 countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…This suggests that tamanaviruses -like other groups within the family Flavivirus -have ancient origins in the animal kingdom. However, despite extensive studies of the viromes of vertebrates [4], with some targeting amphibians and reptiles [21,22], a significant phylogenetic gap still exists between aquatic tamanaviruses and vector-borne flaviviruses. This implies that related tamanaviruses may be found in other vertebrates, such as amphibians and reptiles, but have yet to be discovered.…”
mentioning
confidence: 99%
“…This suggests that tamanaviruses -like other groups within the family Flavivirus -have ancient origins in the animal kingdom. However, despite extensive studies of the viromes of vertebrates [4], with some targeting amphibians and reptiles [21,22], a significant phylogenetic gap still exists between aquatic tamanaviruses and vector-borne flaviviruses. This implies that related tamanaviruses may be found in other vertebrates, such as amphibians and reptiles, but have yet to be discovered.…”
mentioning
confidence: 99%
“…Their evolutionary history is unclear and will likely not be resolved until targeted studies increase confidence in the overall spectrum of hantavirid hosts. The thus-far sporadic discoveries of hantavirids in highly diverse (actinpterygiid and myxinid) fish and (gekkotan and scincomorphan) reptiles [ 74 , 75 , 76 , 77 , 78 ] indicate enormous diversity and imply that hantavirids infect amphibians and possibly crocodilians and their closest relatives, i.e., birds. The latter possibility is supported by at least one publication [ 117 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Hantavirology took another unexpected turn with the metagenomic discovery of three distinct hantaviruses in saltwater actinopterygiid fish of three orders, captured in the South China Sea; one new hantavirus in freshwater actinopterygiid fish, sampled in Europe; one new hantavirus in myxinid fish, captured in the South China Sea; and one new hantavirus in a gekkotan reptile [ 74 , 75 ]. The most recent discovery of additional hantavirus nucleic acids in Australian actinopterygiid freshwater fish and scincomorphan reptiles [ 76 , 77 , 78 ] suggests that there are many more fish and reptile hantaviruses.…”
Section: Viruses In Search Of Diseasesmentioning
confidence: 99%
“…However, serpentoviruses have been detected in free-ranging snakes in North America with no apparent clinical significance to the sampled populations. Moreover, several novel nidoviruses were detected in reptile RNA sequence data, indicating viral diversity in the order Nidovirales in reptiles that has yet to be characterized (Harding et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Much remains to be discovered regarding the distribution and diversity of serpentoviruses in both free-ranging and captive reptiles worldwide. For example, a 2022 study analyzing RNA sequence datasets identified novel nidoviruses in samples from a captive slider turtle ( Trachemys scripta ) from Denmark and a wild Taita blade-horned chameleon ( Kinyongia boehmei ) from Madagascar (Harding et al ., 2022).…”
Section: Host Range and Infection Prevalencementioning
confidence: 99%